The Right to Education in the Convention on the Rights of Persons with Disabilities: How is it Implemented in Indonesia? - Santosa, Satria Aji (Uti Possidetis: Journal of International Law, 2024)
This paper analyses the rights to education for persons with disabilities in Indonesia according to the existing national law and the Convention on the Rights of Persons With Disabilities. It is found that the persons with disabilities are still experiencing ambiguity when it comes to the implementation of their rights to education in Indonesia. This paper concludes that the form of protection of the rights for persons with disabilities to obtain education in Indonesia has not met the criteria set by the Convention on the Rights of Persons With Disabilities because there are still differences in access to education for persons with disabilities in Indonesia. The Indonesian government is suggested to implement the rights to education for persons with disabilities equally and non-discriminatory by ensuring an inclusive access to education and providing special educational facilities for persons with disabilities as regulated in legislation and the Convention on the Rights of Persons With Disabilities.